The Significant Role of CO and NOx in the Tropospheric Ozone Chemistry - K. M. Praseed; Sheela M. Joseph, M. K. Satheesh Kumar, Nishanth. T (Recent Research in Science and Technology, 2010)
Ozone being a greenhouse gas, the chemistry of ozone in the troposphere is considered as an emerging area of investigation after global warming became a reality. The potential role of ozone and its dynamics that changes the atmospheric composition can be retrieved only with the aid of photochemical processes involved in the atmosphere. The various possible chemical reactions that take place at different locations in the atmosphere can significantly change the weather pattern. This is an attempt to review some of the prominent features of the photochemistry of the troposphere and stratosphere.